Losing a Home to Mortgage Foreclosure: Temporary Setback or Chronic Stressor? - Prohaska, Ariane (Social justice, 2013)
The article discusses social stress of home foreclosure as experienced by homeowners in Alabama who have defaulted on their mortgages. Topics include research methodology that involves telephone surveys and an analysis of demographics and policy recommendations for mitigating financial strains that may lead to foreclosure.